Spatial Distribution of Banana Tough Top Disease (BTTD) in Maniema Province, DR Congo - SHADARI, Salumu; MUKANDAMA, Ndolandola; NGAMA, Boloy; SALUMU, Djumaa (European Journal of Science, Innovation and Technology, 2023)
A study on the spatial distribution of banana bunchy top disease (BBTD) in the banana production areas of Maniema was conducted with the aim of determining the incidence and severity of BBTD, the presence and the importance of the Pentalonia nigronervosa vector on the different banana and plantain cultivars grown in this study area of ​​the Province of Maniema. 1890 clumps of banana trees were inspected due to 30 clumps of banana trees per field, 3 fields per village and 3 villages per territory, on seven territories of the Province of Maniema. The selected clumps were analyzed based on key indicators such as: disease incidence, disease severity (BBTD), presence and importance of the vector P. nigronervosa, and the state of farmers’ knowledge compared to the management of BBTD. From the analysis of the results, it was found that BBTD is present throughout the study area with an incidence ranging from 78.52 to 88.15% where the high rate is on banana trees in Kibombo territory (88.15%) and in Pangi (87.05%). Discoloration of leaves with normal size is the most common symptom and also high on banana trees with an average of 31.90%. The vector P. nigronervosa is widespread with an average of 94.85% where a strong presence was found on banana trees in Pangi (97.41%). All the colonies of P. nigronervosa are present on the clumps of banana trees. A large colony with winged insects is the most common form with an average of 40.31%. On the other hand, it should be noted that 100% of banana trees are grown in association with rice, cassava, corn or other crops; 95.24% of farmers use shoots from neighboring fields; the age of the banana plantations surveyed varied from less than 3 years to more than 10 years, i.e. 42.86% of the banana plantations are over 10 years old; 38.10% of banana plantations are 5-7 years old and 8.33% of banana plantations are less than 3 years old. From the analysis of different epidemiological parameters, it was found that the growing conditions of banana plants (cropping systems and other practices) favor the incidence and severity of the disease as well as the presence and importance of the vector P. nigronervosa.